Utilization of Plantain Skin Pectin (Musa paradisiaca L.) as an Edible Coating to Extend the Shelf Life of Red Grapes - Indriasari, Listy; Kusuma, Samuel Budi Wardhana (Indonesian Journal of Chemical Science, 2024)
Red grapes are a fruit that easily rots after harvest. Various methods have been developed to extend the shelf life of grapes post-harvest, such as refrigeration and fumigation with sulfur dioxide. However, this preservation method is considered less efficient. Therefore, better preservation methods are needed, such as providing edible coating. Edible coating can be made from pectin compounds extracted from Kepok banana peels. Kepok bananas are a type of banana that is widely consumed by Indonesian people. In this study, kepok banana peel pectin was extracted using the UAE method. The coating of red grapes is carried out using the dipping method, with varying times of 5, 10, and 20 minutes. The aim of this research was to determine the characteristics of kepok banana peel pectin, the effect of dipping time and storage temperature on the characteristics of red grapes. The results of pectin extracted from Kepok banana peels in this study included low methoxy pectin with a yield of 2.11%. Different immersion times and storage temperatures showed an influence on the characteristics of red grapes. The smallest weight loss was obtained when the immersion time was 5 minutes at refrigerator temperature (0.65%). The best water content was obtained in the immersion treatment time of 5 minutes at room temperature (86.81%). Vitamin C levels can be maintained by immersion treatment for 20 minutes at refrigerator temperature (2.96%). The smallest color difference was obtained when the dyeing time was 10 minutes at refrigerator temperature (6.69%).